Detection acoustic signals of partial discharges on defects in high voltage insulation - D. A. Ivanov; T. G. Galieva; A. V. Golenishchev-Kutuzov; M. F. Sadykov; R. I. Kalimullin; A. V. Semennikov (Омский научный вестник)
The article is devoted to the method of acoustic registration of partial discharges in high-voltage insulators. Physical processes of generation of various types of partial discharges in high-voltage insulators are considered. The instrumental implementation and method of processing diagnostic information from sensitive elements — acoustic receivers of the ultrasonic range are described. The ability to detect sources of partial discharges with reference to the place of origin is important for localizing a faulty element and its further diagnosis.